Rosa roxburghii-edible fungi fermentation broth attenuates hyperglycemia, hyperlipidemia and affects gut microbiota in mice with type 2 diabetes. (April 2023) - Hu, Xiaoyi; Hu, Jielun; Leng, Tuo; Liu, Shuai; Xie, Mingyong
Abstract: Type 2 diabetes (T2D) is a worldwide chronic disease, which is associated with metabolic disorders and gut microbiota imbalance. The anti-diabetic effects of two fermentation broth composed of Rosa roxburghii and edible fungi in different proportions (FBA and FBB) were studied using a high-fat diet combined with streptozotocin-induced type 2 diabetes mouse model. Our results revealed that intervention with FBA and FBB could ameliorate body weight loss, blood glucose, insulin, blood lipids, morphology of the kidney and liver, and oxidative stress levels in diabetic mice. Furthermore, FBA and FBB interventions significantly improved the community richness and diversity of gut microbiota. Supplementation with FBA and FBB increased the relative abundance of some beneficial and SCFAs-producing genus such as Bifidobacterium, Prevotella, Ruminococcus, Clostridium, and Allobaculum, and also increased the levels of SCFAs in the colonic contents. These results indicated that FBA and FBB can be used as promising functional foods for preventing or alleviating diabetes through modulating gut microbiota and production of SCFAs. Graphical abstract: Image 1 Highlights: Treated with FBA and FBB could alleviate hyperglycemia and hyperlipidemia in diabetic mice. FBA and FBB interventions significantly improved the community richness and diversity of gut microbiota. Supplementation with FBA and FBB increased the relative abundance of some beneficial and SCFAs-producing genus. FBA and FBB treatment promoted the production of short-chain fatty acids in colonic contents.